Control-ownership patterns in Turkey-listed firms - Mustafa, Aree S; Che Ahmad, Ayoib; Chandren, Sitraselvi (2016)
The motivation of this study stems from the importance of protecting investors’ rights, and particularly those of minority shareholders.This study addresses the predominant control-ownership structure of the top 100 firms listed in Bursa Istanbul (BI) using the data for 2015. It shows the most common control-ownership structure within business groups, in which shareholders exercise control over a group of firms and maintain a small stake of firms’ equities.Turkish firms are categorised with highly concentrated ownership and families’ being the dominant shareholders owning more than 80% of all publically listed firms in BI.The results of the study indicate that the divergence between cash rights and control rights (wedge) in the top 100 Turkish firms is mainly achieved through a pyramidal ownership structure, dual class shares, and cross-ownership at about 41%, 40%, and 11%, respectively, while approximately 8% of firms do not use wedge.Hence, wedge exacerbates Type II Agency problems.This paper calls for future research to study the environment of the wedge for Turkish firms listed in BI